Let f ( x ) = x 3 − 2 3 x 2 + x + 4 1 . Find the value of
∫ 4 1 4 3 f ( f ( x ) ) d x 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is insane, ridiculous. Means how you got the note!. I calculated f(1-x) only and did not note the latter part .
I was actually trying to calculate f(f(x)) repeatedly but in vain.
Again thanks a lot for sharing it.
Log in to reply
You have a set of good question. I have provided solution to Not defined Really you have asked me earlier.
Log in to reply
I am not blaming sir.
I am just realizing the steps. Nothing else.
Done the same sir
Problem Loading...
Note Loading...
Set Loading...
I ⟹ I 1 = ∫ 4 1 4 3 f ( f ( x ) ) d x = 2 1 ∫ 4 1 4 3 f ( f ( x ) ) + f ( f ( 1 − x ) ) d x = 2 1 ∫ 4 1 4 3 f ( f ( x ) ) + f ( 1 − f ( x ) ) d x = 2 1 ∫ 4 1 4 3 f ( f ( x ) ) + 1 − f ( f ( x ) ) d x = 2 1 ∫ 4 1 4 3 d x = 4 1 = 4 Using the identity: ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x See note: f ( 1 − x ) = 1 − f ( x ) Again f ( 1 − f ( x ) ) = 1 − f ( f ( x ) )
Note:
f ( x ) ⟹ f ( 1 − x ) = x 3 − 2 3 x 2 + x + 4 1 = 4 3 − x + 2 3 x 2 − x 3 = 1 − ( x 3 − 2 3 x 2 + x + 4 1 ) = 1 − f ( x )